2015
DOI: 10.3892/ol.2015.3117
|View full text |Cite
|
Sign up to set email alerts
|

Rana catesbeiana ribonuclease induces cell apoptosis via the caspase-9/-3 signaling pathway in human glioblastoma DBTRG, GBM8901 and GBM8401 cell lines

Abstract: Abstract. Human glioblastoma multiforme is one of the most aggressive malignant brain tumor types, and the mean survival time of patients with a brain tumor is <2 years when traditional therapies are administered. Thus, numerous studies have focused on the development of novel treatments for brain tumors. Frog ribonucleases, such as Onconase and Rana catesbeiana ribonuclease (RC-RNase), exert antitumor effects on various tumor cells, including cervical cancer, breast cancer, hepatoma, leukemia, pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Although SBL has been reported to activate caspase-3/7 ( 3 , 5 , 18 ), known as the major executioner caspases, the molecular mechanism remains unclear. Indeed, the caspase-3/7 activity in SBL-treated MDA-MB231 cells was 22-fold higher than that in the untreated cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SBL has been reported to activate caspase-3/7 ( 3 , 5 , 18 ), known as the major executioner caspases, the molecular mechanism remains unclear. Indeed, the caspase-3/7 activity in SBL-treated MDA-MB231 cells was 22-fold higher than that in the untreated cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The internalization of SBL into cancer cells causes the degradation of ribosomal RNA, which leads to the inhibition of protein synthesis and, in turn, induces cell death ( 8 , 12 , 13 ). SBL-induced cell death is accompanied by mitochondrial dysfunction ( 14 ), endoplasmic reticulum stress ( 15 ), autophagocytosis ( 16 ), and caspase activation ( 3 , 5 ). Our previous studies showed that mitogen-activated protein kinases (MAPKs) were phosphorylated in two SBL-treated cell lines, human T-cell leukemia Jurkat cells and malignant mesothelioma NCI-H28 cells ( 14 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cSBL acts as an anti-cancer agent against various human cancer cells including carcinoma (cervical, oral, hepatocellular, and breast), leukemia, lymphoma, mesothelioma, and glioblastoma [ 24 , 41 , 42 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Interestingly, although cSBL induces apoptosis in those cancer cells, normal tissue-derived cells, such as fibroblasts, melanocytes, keratinocytes, and mesothelial cells, are relatively insensitive to this agent [ 53 , 56 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, as Aristotle would suggest, in medio stat virtus. When inside the cell, SBLc activates the intrinsic apoptotic pathway on more than 30 tumor cell lines representing leukemia [107][108][109]118,120,131,132], Burkitt's lymphoma [108,109], cervical [133], hepatocellular [120,121,133], and estrogen-positive and -negative breast carcinomas [113,114,116,117,120], glioblastoma [119], and malignant mesothelioma [110,113] (Table 3).…”
Section: Rana Catesbeianamentioning
confidence: 99%
“…For the record, pemetrexed, which is one of the drugs of choice currently used for the cure of mesothelioma, failed to eradicate murine MSTO-xenografted tumors on the same experimental conditions [113]. In addition, SBLc effectively inhibited the growth of glioblastoma tumors in nude mice once again without causing any side effect [119].…”
Section: Rana Catesbeianamentioning
confidence: 99%